Influence of liquefied and CCB containing liquefied wood on growth of wood decay fungi - Hrastnik, D.; Budija, F.; Humar, M.; Petric, M. (Maderas. Ciencia y Tecnología, 2025)
There are high amounts of post-consumed protected waste wood removed from service every year. The residual biocides, including copper, chromium and boron from CCB (Cu, Cr, B) in post-consumed wood that was protected with biocides may cause environmental problems during waste management, for example during land filling. Therefore, the aim of this study was to find out if Cu and Cr in the processed waste wood, previously treated with CCB, can be re-used as a wood preservative or in coatings made of liquefied wood. Liquefaction of CCB containing waste wood could be as well the first step in the elimination process of metals. So, the optimal conditions for liquefaction of CCB (Cu, Cr and B) containing black poplar (Populus nigra L.) wood were established and compared with liquefaction of uncontaminated black poplar wood. The reactants for liquefaction of black poplar wood sawdust were ethylene glycol (EG) and sulphuric acid. It was observed that in the last stages of the liquefaction process, the presence of Cu, Cr and B did not have any influence on liquefaction yield (LY), while their influence was observed in first stages of the solvolytic reaction. Investigations of fungicidal properties of uncontaminated and CCB containing liquefied wood showed higher antifungal efficacy of liquefied wood without Cu, Cr and B than of liquefied wood that contained CCB. In the tested concentration range, the presence of Cu even promoted the growth of selected wood decay fungi. One of the reasons for higher toxicity of liquefied black poplar sawdust without Cu, Cr and B, was its very low pH value.